Interdisciplinary Collaboration in Healthcare Systems: An Empirical Study - Taskin, Nazim; Harsini, Ali Intezari; Verville, Jacques; Keskin, Tayfun (ACIS, 2014)
A review of the literature of social work and healthcare systems reveals that in spite of the numerous arguments that have been provided as to the importance of identifying and managing the supportive or hindering factors in interdisciplinary collaboration, there are still many questions that the relevant literature leave unanswered. This paper reports on an empirical study that investigates the factors that associated with interdisciplinary collaboration in the field of social work. The study findings show that collaboration among interdisciplinary professional engages various elements including ‘Collective ownership of Goals’, ‘Reflection on process’, ‘Interdependence’, ‘Communication’, ‘Openness’, and ‘Trust’. The findings also reveal that there are relationships among some of the factors, facilitating interdisciplinary collaboration. The study will have significant contribution to both theory and practice in the field of social work. While the findings shed light on the elements involved in interdisciplinary collaboration, the findings also can be used as framework towards improving social services.